Leadership insights for wizards and witches - Simha, Aditya (Exploring effective leadership practices through popular culture, 2022)
Popular culture can help us think creatively and teach us the best ways to use our imagination. Leadership Insights for Wizards and Witches outlines various leadership styles, theories, and concepts through the imaginative lens of J.K. Rowling's magical world - from ethical, servant, and authentic leadership, to power, influence, and persuasion. Combining the immersive and enchanting context of the series with the scholarly discipline of leadership, Simha teaches key theories using examples of characters and situations familiar to fans. Leadership Insights for Wizards and Witches encourages readers to consider how they themselves can approach personal and organizational problems by finding solutions using insights and perspectives gathered from the discipline of leadership. Readers will gain a vital understanding of how not to lead for a holistic mastery of leadership. Leadership Insights for Wizards and Witches harnesses surprisingly relatable examples from the renowned mystical stories and movies to inform a variety of readers, ranging from high school students to undergraduate students and professional practitioners - and of course fans everywhere - regardless of professional backgrounds and experience. The Exploring Effective Leadership Practices through Popular Culture series breaks down leadership theories, making them clearer, manageable, and easier to put into practice.